Newfoundlanders Remember Their Past - Josiah Kearley - Memorial University of Newfoundland. Extension Service
Newfoundlanders Remember Their Past is a 5 part television series that was created by Extension Service, Memorial University of Newfoundland for Memorial University Television to highlight some of the films and interviews done in the past through Extension Services. Some of the film series that will be highlighted in this series is from Decks Awash, I can mind the time. and the Port au Choix Project. In this first episode of the series host Charles Callanan looks at the film series "I can mind the time.", specifically the film "I can mind the time. Josiah Kearley" which highlights the life of Josiah (Joe) Kearley, one of the orginal charter members of the Fishermen's Protection Union (FPU). As an introduction to the film Charles Callanan interviews Paul McCleod who was involved in the original filming of this interview.